The Potential of Coir Composite in The Production of Spare Parts and Equipment for Vehicles Transporting Goods by Road and Water - Nguyen, Dinh Tuyen; Nguyen, Thi Bich Ngoc (International Journal of Advanced Science Computing and Engineering, 2020)
Traditional materials used in the production of industrial equipment parts are now wood and metal. But these materials are gradually scarce, the need to find alternative materials is necessary. On that basis, there have been many studies on fiber reinforced composites in which glass fiber reinforcement is widely applied. However, fiberglass-reinforced composites are difficult to decompose and recycle, leading to serious environmental impacts. To solve this problem, scientists are working to apply bio-fibers to replace glass fibers. In recent years, there have been many studies on coir fiber and its application in the manufacture of coir fiber fortified composites. This article reviews the potential of coir fiber fortified materials applied in the production of industrial products.